Delivering evidence to prevent recurrent venous thromboembolism in pregnancy - van Lennep, Jeanine E Roeters; Nerenberg, Kara A (The Lancet (British edition), 2022)
Compared with non-pregnant women, pregnant women and women in the post-partum period until 12 weeks have a 4–5-times increased risk of venous thromboembolism, with an incidence of approximately 0·1%.1 Women with a previous venous thromboembolism have higher risks (2–10%) of recurrent venous thromboembolism in pregnancy and post partum than do other women.2 Increased venous thromboembolism risks are due to physiological changes in pregnancy contributing to all three components of Virchow's triad: hypercoagulability, stasis of flow, and endothelial damage.2 International clinical practice guidelines recommend low-molecular-weight heparin thromboprophylaxis during pregnancy and until 6 weeks post partum in women with previous venous thromboembolism. [...]enrolment of patients up to 14 weeks' gestational age might have introduced selection bias, although less than 50% of participants in both groups were on low-molecular-weight heparin before randomisation. The incremental benefit of another randomised controlled trial specifically to determine the post-partum dose of venous thromboembolism might be outweighed by the methodological challenges, because Highlow took 7 years to recruit 1110 participants, had a low event rate, high proportion of protocol deviations by clinicians, and challenges with patient adherence. [...]research focused on understanding perspectives among pregnant women, barriers to participating in medication trials, and clinicians' willingness to challenge non-evidence-based routine care, as well as strategies for implementation of current guidelines, might achieve greater reductions in venous thromboembolism in pregnancy and post partum while balancing limited research resources.